2018
DOI: 10.1007/s00192-018-3738-8
|View full text |Cite
|
Sign up to set email alerts
|

Profile and outcome of patients with recurrent urogenital fistula in a fistula centre in Nigeria

Abstract: The success rate was good. Patients who had previous failed repairs at the fistula centre had better outcomes after the repeat surgeries. Centralizing fistula care will enhance optimal outcomes. It may also boost training and research in this specialty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…We were able to demonstrate one factor with predictive value for successful surgical outcome. In another study on patients with recurrent fistulas, significant associations were demonstrated between the number of previous repairs, age, fistula classification, duration of the fistula, surgeon's experience, and the place where the repair was attempted [18]. However, no multivariate analysis was performed to control for confounders and probably most significance would be lost if a multivariate analysis were used, as shown in our study.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…We were able to demonstrate one factor with predictive value for successful surgical outcome. In another study on patients with recurrent fistulas, significant associations were demonstrated between the number of previous repairs, age, fistula classification, duration of the fistula, surgeon's experience, and the place where the repair was attempted [18]. However, no multivariate analysis was performed to control for confounders and probably most significance would be lost if a multivariate analysis were used, as shown in our study.…”
Section: Discussionmentioning
confidence: 50%
“…The median surgery time was 1:00 [0:40-1:25] h with an estimated blood loss of 50.0 [20-100] ml. The median duration of postoperative catheterization was 14 [14][15][16][17][18][19][20] days.…”
Section: Baseline Characteristicsmentioning
confidence: 99%
“…We also examined the association between fistula classification and successful repair outcome, despite the included studies lacking consistency in classification methods. Out of the seven studies included for the examination of the effect of classification on successful repair outcome, three studies used the Goh classification [ 21 , 40 , 44 ] method and four studies used the Waaldijk classification method [ 51 , 52 , 69 , 76 ]. We analyzed the findings of reports in both classifications after categorizing them into Grade II and above, and Grade I.…”
Section: Discussionmentioning
confidence: 99%
“…56.2%, 50%, and 0%, respectively. 9 Different initiatives such as the United Nations Population Fund (UNFPA), Maternal Health Task Force (MHTF), countdown, Global Strategy for Women's health, and others have devoted efforts to reducing preventable maternal mortality. 10,11 Despite such efforts, obstetric fistula still compromises the well-being of affected women in all dimensions of their health.…”
Section: Introductionmentioning
confidence: 99%